Civilizing rituals inside public art museums - Duncan, Carol (Routledge, 1995)
Public art museums have become necessary fixtures of every city or country with any claim to importance. Yet we have still to understand what happens in them. Civilizing Rituals treats art museums from a new perspective--as ritual settings in their own right and as cultural artifacts that are much more than neutral shelters for art.